Shell EIA rectification process: Gauteng Province sites - Gbandi, Vivien; Raji, Racheal; Young, Aaron; Chaka, Isheunesu (Department of Environmental and Geographical Science, 2024)
The second-year Master of Philosophy students in the Department of Environmental and Geographical Sciences at the University of Cape Town were invited to participate in the completion of Rectification Reports for fuel storage installations in Gauteng. The Masters group consisted of four members who travelled to Gauteng for two weeks during March 2007 in order to complete site inspections of the fuel tanks. After returning to Cape Town, reportwriting commenced and draft reports for each site were submitted to ERM for final approval before being submitted to the Gauteng Department of Agriculture, Conservation and Environment (GDACE).